Respon Siswa Terhadap Media Educaplay sebagai Evaluasi Praktikum Reaksi Eksoterm dan Endoterm - Maghfiroh, Diah Laeli; 'Azmi, Madah Ikrimatul (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This study describes students' responses to Educaplay as a post-practical evaluation tool for exothermic and endothermic reactions. Methodology/approach: Using a descriptive method, data from 27 eleventh-grade students were collected via Educaplay quiz scores, observations, and interviews, then analyzed using descriptive statistics and thematic analysis. Findings: Quiz scores averaged 70.37 (range: 50–90), indicating good conceptual understanding. Cognitively, the relevant questions facilitated conceptual reflection. Affectively, Educaplay's game-like interface and immediate feedback boosted enthusiasm and motivation. Technically, challenges like limited internet and time constraints remained. Practical implications: T Educators can use Educaplay for interactive diagnostic assessment, provided it is combined with deeper data interpretation methods and supported by adequate school infrastructure. Originality/value: This study uniquely evaluates Educaplay specifically as a post-chemistry lab assessment, comprehensively analyzing student responses across cognitive, affective, and technical dimensions rather than just general cognitive achievement.